Proceedings of the 22nd International Conference on Industrial Engineering and Engineering Management 2015 Innovation and Practice in Industrial Engineering and Management (Volume 2) - Qi, Ershi; Shen, Jiang; Dou, Runliang; SpringerLink (Online service) (Paris : Atlantis Press : Imprint: Atlantis Press, 2016)
Being the premier forum for the presentation of new advances and research results in the fields of Industrial Engineering, IEEM 2015 aims to provide a high-level international forum for experts, scholars and entrepreneurs at home and abroad to present the recent advances, new techniques and applications face and face, to promote discussion and interaction among academics, researchers and professionals to promote the developments and applications of the related theories and technologies in universities and enterprises, and to establish business or research relations to find global partners for future collaboration in the field of Industrial Engineering. All the goals of the international conference are to fulfill the mission of the series conference which is to review, exchange, summarize and promote the latest achievements in the field of industrial engineering and engineering management over the past year, and to propose prospects and vision for the further development. This volume is the second of the two proceedings volumes from this conference.
A Comparative Study on Retailer's Refunding Strategies Considering Products Advance Selling -- Research on the Monopolist' Repurchase and Remanufacture Decisions Based on Heterogeneous Consumer Considering Buy-back Cost -- Study on the Exchange Rate Risk of China International Construction Enterprises -- Technology Diffusion and Acquisition Premium in M&A -- Coordinated Development Degree of County Socio-economic System Prediction Based on GA-SVM -- Quality Safety Risk Analysis on Children's Car Safety Seat -- Coupling Relationship Analysis of Economic Growth and Environmental Pollution in Western Region -- The dynamic analysis of R&D competition behavior of a duopoly under the condition of different expectations -- Strategic Human Capital in Organization: Frontier Review, Prospective Commentary, and Guiding Framework -- Research on the Effects of the Fixed Asset Investment on the Non-performing Loans Ratio -- Research on Real-time cost control in factory in IT environment.
Keywords: Industrial Management; Construction industry -- Management; Industrial Management; Construction Management